Identifying Dominant Structural Pattern of Semarang City Using Digital Elevation Model and Landsat 8-OLI Imagery - Hidayatillah, Ahmad Syauqi; Nurcahyo, Tri Apri; Muliawan, Jody Bintara Pradiksa; Endarsih, Alfyah Edina (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Semarang City is an area in the northern part of Java Island, administratively the Capital of Central Java Province. Because Semarang City is the provincial capital, Semarang City has a relatively dense population. Geologically, the city of Semarang is an area that consists of various types of lithology and is traversed by various regional geological structures. In this case, understanding the existence and distribution of geological structures in the city of Semarang is essential, considering that geological structures are one of the controllers for natural disasters such as landslides and earthquakes. This study analyzed the existence and distribution of geological structures in the city of Semarang based on the lineaments observed from digital elevation models and satellite imagery. This study aims to identify the dominant structural pattern in Semarang City, determine the relationship between fault fracture density (FFD) with regional geological structure and lithology, and determine the fault zone area in Semarang City based on FFD & lineament analysis. The method used in this analysis is to process DEM data and Landsat 8-OLI imagery, then interpret the lineaments in the form of rosset diagrams and the density in the form of FFD maps. The results of the rosset diagram analysis show that Semarang City has various structural lineament patterns, namely: North–South, Northeast–Southwest, and Northwest–Southeast, with the North–South pattern as the dominant pattern. Based on the results of the lineament density distribution on the FFD map, it is known that the area traversed by the Semarang regional geological structure has a high lineament density value which is interpreted that the area is a weak zone with high structural intensity. From this study, it can also be seen that there is no significant relationship between the type of lithology and the density value on the FFD map. The distribution of lineament density is not affected by the type of lithology, except in the northern and northeastern parts of Semarang city, which consist of alluvium. Based on these results, it can be interpreted that the fault zone area is associated with areas that have high-density values on the FFD map. Distribution of the fault zone area of Semarang City is spreading over the Banyumanik, Gunungpati, and Mijen Districts, which are relatively in the southern and central parts of Semarang City.